2016
DOI: 10.1177/0963662516638634
|View full text |Cite
|
Sign up to set email alerts
|

How scary! An analysis of visual communication concerning genetically modified organisms in Italy

Abstract: Several studies provide evidence of the role of written communication in influencing public perception towards genetically modified organisms, whereas visual communication has been sparsely investigated. This article aims to evaluate the exposure of the Italian population to scary genetically modified organism-related images. A set of 517 images collected through Google are classified considering fearful attributes, and an index that accounts for the scary impact of these images is built. Then, through an ordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 72 publications
1
13
0
Order By: Relevance
“…In sum, as would be predicted by negativity bias (Baumeister, Bratslavsky, Finkenauer, & Vohs, 2001; Rozin & Royzman, 2001), the news shared through media is likely to be more negative than actual data would warrant and, indeed, most consumers appear to perceive it this way (e.g., Blancke et al, 2015; Cui & Shoemaker, 2018; Ventura et al, 2016). This bias may help to explain why, though there are many more studies that find GMFs to be safe than those that find otherwise, these many “positive” studies (that scientists bear in mind and draw on in their conclusions) routinely “go unnoticed in [GMF] public debate” (Sánchez & Parrott, 2017, p. 1227).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…In sum, as would be predicted by negativity bias (Baumeister, Bratslavsky, Finkenauer, & Vohs, 2001; Rozin & Royzman, 2001), the news shared through media is likely to be more negative than actual data would warrant and, indeed, most consumers appear to perceive it this way (e.g., Blancke et al, 2015; Cui & Shoemaker, 2018; Ventura et al, 2016). This bias may help to explain why, though there are many more studies that find GMFs to be safe than those that find otherwise, these many “positive” studies (that scientists bear in mind and draw on in their conclusions) routinely “go unnoticed in [GMF] public debate” (Sánchez & Parrott, 2017, p. 1227).…”
mentioning
confidence: 87%
“…Though various media sources are not always evidence-based, they often cite actual data, including empirical findings that speak to GMFs’ likely risks (see Nicolia et al, 2014, and Saletan, 2015, for discussion), as well as government bans on GM imports and production and scientific dissent regarding GMFs’ current safety (Hilbeck et al, 2015; Krimsky, 2015; Tsatsakis et al, 2017 3 ). Anti-GMO “factoids” are commonly represented in a visually striking manner (e.g., tomato with claws or fish scales; Ventura, Frisio, Ferrazzi, & Siletti, 2016) that renders them highly “available” (Tversky & Kahneman, 1973).…”
mentioning
confidence: 99%
“…The attitude in cartoons toward GMOs was divided into approving, neutral, and opposing (Supplemental Figure 2). The code for scary information was determined with reference to the code for Italian GMO images described in Ventura et al (2017). The coding and detailed description of each variable is shown in Supplemental Table 2.…”
Section: Methods and Datamentioning
confidence: 99%
“…However, the vast majority of GMO studies have analyzed written communication, whereas visual communication has been sparsely investigated. Vera Ventura et al (2017) collected numerous GM images from Google and built an index illustrating the scary impact (SI) of these images. In a study on Spanish Darwin cartoons, Domínguez and Mateu (2013) found that the controversy of Darwinism and religion has been lurking in Spanish society.…”
Section: Introductionmentioning
confidence: 99%
“…They help the audience understand complicated scientific issues and reveal the contestations of various social actors in interpreting scientific controversies. While GMOs have sparked heated debate since the 1970s and is still one of the scientific issues on which a sizable divergence exists between scientists and the public (Pew Research Center, 2016b), news coverage of GMOs in recent years has become more balanced in presenting benefits and risks (Bonfadelli et al, 2002; Ventura et al, 2017). In covering GM applications in biotechnology, subtle ways of framing with negative connotations are evident without open oppositions (Ventura et al, 2017).…”
Section: Theoretical Frameworkmentioning
confidence: 99%